Community views on 'Can perinatal services safely identify Aboriginal and Torres Strait Islander parents experiencing complex trauma?'. (26th April 2022) - Chamberlain, Catherine; Gray, Paul; Herrman, Helen; Mensah, Fiona; Andrews, Shawana; Krakouer, Jacynta; McCalman, Pamela; Elliott, Alison; Atkinson, Judy; O'Dea, Birri; Bhathal, Alex; Gee, Graham
Abstract: Family and extended kinship systems which nurture healthy, happy children are central to Aboriginal and Torres Strait Islander cultures. Since colonisation, Aboriginal and Torres Strait Islander communities have been impacted by intergenerational cycles of trauma, stemming from colonial violence, genocidal policies and discrimination, including the forced removal of children from their families. Becoming a parent offers a unique life‐course opportunity for trauma recovery and preventing intergenerational trauma. However, identifying or 'recognising' complex trauma carries significant risk of harm for Aboriginal and Torres Strait Islander parents due to reactive prenatal child protection involvement potentially compounding experiences of trauma, and limited benefits due to lack of culturally appropriate support. The Aboriginal‐led participatory Healing the Past by Nurturing the Future project aims to co‐design safe, accessible and feasible perinatal awareness, recognition, assessment and support strategies for Aboriginal and Torres Strait Islander parents experiencing complex trauma. This paper presents views of 38 workshop participants to determine prerequisites for ensuring benefits outweigh risks of assessment to safely recognise parents experiencing complex trauma, consistent with screening criteria. Six essential elements were identified from thematic analysis: high‐quality holistic care; cultural, social and emotional safety; empowerment, choice and control; flexible person‐centred approaches; trusting relationships; and sensitive, skilled communication. Key Practitioner Messages: The impacts of colonisation and rates of Aboriginal and Torres Strait children in out‐of‐home care mean that there can be a myriad of issues facing Aboriginal and Torres Strait Islander parents with regard to perinatal child protection involvement. The benefits must outweigh the risks of identifying parents experiencing complex trauma. Assessment must be offered within foundations of supportive relationships and holistic care in culturally‐safe, empowering settings, where choices are respected and skilled communication approaches are used.